2017
DOI: 10.1155/2017/6952407
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Characterization of Smallholders’ Feeding Practices with On-Farm Feeding Trials to Improve Utilization of Crop Residues on Smallholder Farms

Abstract: This study characterized wheat straw feeding practices in smallholder farms using cross sectional survey and the results informed the design of an experiment to improve the nutritive value of wheat straw with urea and yeast culture treatment. Three diets tested in 49 days' feeding trial were farmers' rainy season feeding practice (FP), addition of urea to wheat straw at the time of feeding (USWS), and 14 days' incubation of straw with urea (UTWS). Yeast culture (15 g/day) was mixed with commercial dairy meal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 10 publications
(10 reference statements)
0
7
0
Order By: Relevance
“…Treating with urea generates gaseous ammonia and carbonic gas, which spread and treat forages and ensure good conservation and quality [4,3]. This ensures the breakdown of chemical bonds between lignin, hemicellulose and cellulose, which are respectively indigestible, partially digestible or completely digestible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treating with urea generates gaseous ammonia and carbonic gas, which spread and treat forages and ensure good conservation and quality [4,3]. This ensures the breakdown of chemical bonds between lignin, hemicellulose and cellulose, which are respectively indigestible, partially digestible or completely digestible.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, ruminant animals largely depend on cereal straws which are low in protein and available energy [2,3]. Chemical treatment and/or supplementation with protein sources were used to improve the quality of these straws [2,4] However, research for development projects have accorded more attention on urea treatment due to its advantage of improving intake, digestibility and nitrogen content and reducing the use of concentrate [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, roughages, being more fibrous in nature during the dry season require that their quality be upgraded through supplementation for effective utilization by dairy cattle. [56], demonstrated that dairy cows fed with ureatreated wheat/rice straw had similar milk yield to that of cows feed with fresh grass. However, milk of the cows fed urea treated wheat/rice straw had a higher milk fat content and net income as compared with the milk produced by cows fed un-treated straw or fresh grass.…”
Section: Roughage Quality and Quantitymentioning
confidence: 99%
“…Further, also during the wet season period the nutrient content of natural grasses on average is about 25% dry matter; 10% crude protein; 6% ash and a fibre content of 35% crude fibre or 43% acid detergent fibre (ADF) [41]. As the dry season advances and conditions become severe, their nutritional quality declines to the extent that crude protein could fall to as low as 2% [56]. Ash values also decline to about 3 to 4% as a result of translocation to the root system, while fibre content increases in response to the process of lignification, and sometimes the crude fibre could be as high as 50 or 60% ADF [57,58].…”
Section: Roughage Quality and Quantitymentioning
confidence: 99%
“…Fodder scarcity is most severe in the dry season (Lukuyu et al, 2009). At the same time, several technologies for improving quantity and quality of fodders are available, such as improved fodder species, technologies for conserving fodder, ration formulation, and chemical treatments, such as using urea or ammonia, or biological treatment using fungi and bacteria to improve quality of straws (Kashongwe et al, 2017b;Kebebe et al, 2017;Lukuyu et al, 2011;Musalia et al, 2016;Thornton and Herrero, 2015). The adoption rate of feeding technologies by smallholders, however, is low, i.e.…”
Section: Biophysical Constraintsmentioning
confidence: 99%